HUBUNGAN RESPONSE TIME PERAWAT DENGAN PENANGANAN KELUHAN (COMPLAINT HANDLING) KELUARGA PASIEN KECELAKAAN LALU LINTAS DALAM PELAYANAN KEPERAWATAN DI INSTALASI GAWAT DARURAT - Efendi, Suradi; Masdah, Siti; Hartati, Sri; Sarimin, Dorce Sisfiani; Rondonuwu, Rolly Harvie Stevan (Ensiklopedia of Journal, 2024)
Complaint handling is one of the factors that affect the quality and satisfaction of clients. Complaint handling can be known by how to handle complaints from patients. Nurses need to improve the quality of nurse response and Complaint handling in serving patients. The purpose of this study was to determine the relationship between nurse response time and complaint handling of families of traffic accident patients in nursing services at the Emergency Department of Dumai City Hospital. Correlational study research design with 98 respondents. The sampling technique was purposive sampling. The results of the Spearmen rank test analysis showed that there was a relationship between nurse response time and complaint handling in the emergency room of the Dumai City Hospital (p=0.000 <α). It is expected that the management of Dumai City Hospital can make input in making nursing service policies in meeting patient needs.Keywords: Complaint handling, Nurse, Response Time